2007
DOI: 10.1128/mcb.01512-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phosphocholine Cytidylyltransferase α in Lung Development

Abstract: Lung development depends upon the differentiation and expansion of a variety of specialized epithelial cell types, including distal type I and type II pneumocytes in the late term. Previous studies have shown a strict dependence on the choline cytidylyltransferase ␣ isoform (CCT␣) to mediate membrane phospholipid formation in cultured cells and during preimplantation embryogenesis. CCT␣ expression is highest in lung, and there has long been speculation about its precise role, due to the dual requirement for ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 52 publications
3
41
0
Order By: Relevance
“…Dipalmitoyl-PC in lungs of the knockout mice, as well as in the alveolar lavage, was significantly reduced. Thus, CTa is not required for proliferation or differentiation of lung epithelia but is essential for normal PC secretion by the lung (35).…”
Section: Phospholipid Knockout Mice S133mentioning
confidence: 99%
See 1 more Smart Citation
“…Dipalmitoyl-PC in lungs of the knockout mice, as well as in the alveolar lavage, was significantly reduced. Thus, CTa is not required for proliferation or differentiation of lung epithelia but is essential for normal PC secretion by the lung (35).…”
Section: Phospholipid Knockout Mice S133mentioning
confidence: 99%
“…The Pcyt1a gene was selectively inactivated in mouse lung epithelial cells (35). Lack of CTa did not impair lung development, but at birth, the mice suffered respiratory failure.…”
Section: Phospholipid Knockout Mice S133mentioning
confidence: 99%
“…However, CCT␣ Ϫ/Ϫ primary animal cells survive and differentiate, as exemplified by macrophages (13), hepatocytes (19), lung alveolar cells (18), and B-cells (this study). These results strongly suggest that another source of PtdCho is available that circumvents a requirement for CCT␣.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of CCT␣ in adult animals have been studied by tissue-specific deletion of CCT␣ gene expression using the Cre-loxP system. These studies have revealed distinct roles for CCT␣ in professional secretory cells, including the formation and secretion of surfactant by alveolar epithelial cells (18), the assembly and secretion of lipoproteins by hepatocytes (19), and cytokine secretion by stimulated macrophages (20). In this study, the role of CCT␣ in B lymphocyte function was examined by selectively deleting the Pcyt1a gene encoding CCT␣ in murine B-cells.…”
mentioning
confidence: 99%
“…For example, knockout of the ubiquitous CCT ␣ isoform in mice is embryonic lethal, indicating an essential developmental role ( 5 ). However, conditional CCT ␣ deletion in tissues that express suffi cient CCT ␤ or phosphatidylethanolamine Nmethyltransferase is not lethal, resulting in phenotypes related to partial deduction in biosynthetic capacity (6)(7)(8).…”
mentioning
confidence: 99%